Beyond advising and mentoring: Competencies for coaching in medical education. (3rd October 2021) - Wolff, Meg; Deiorio, Nicole M.; Miller Juve, Amy; Richardson, Judee; Gazelle, Gail; Moore, Margaret; Santen, Sally A.; Hammoud, Maya M.
Abstract: Background: Coaching supports academic goals, professional development and wellbeing in medical education. Scant literature exists on training and assessing coaches and evaluating coaching programs. To begin filling this gap, we created a set of coach competencies for medical education using a modified Delphi approach. Methods: An expert team assembled, comprised of seven experts in the field of coaching. A modified Delphi approach was utilized to develop competencies. Results: Fifteen competencies in five domains resulted: coaching process and structure, relational skills, coaching skills, coaching theories and models, and coach development. Conclusion: These competencies delineate essential features of a coach in medical education. Next steps include creating faculty development and assessment tools for coaching.